Inheritance patterns of ATCCT repeat interruptions in spinocerebellar ataxia type 10 (SCA10) expansions. - Ivette Landrian; Karen N McFarland; Jilin Liu; Connie J Mulligan; Astrid Rasmussen; Tetsuo Ashizawa (PLoS ONE, 2017)
Spinocerebellar ataxia type 10 (SCA10), an autosomal dominant cerebellar ataxia disorder, is caused by a non-coding ATTCT microsatellite repeat expansion in the ataxin 10 gene. In a subset of SCA10 families, the 5'-end of the repeat expansion contains a complex sequence of penta- and heptanucleotide interruption motifs which is followed by a pure tract of tandem ATCCT repeats of unknown length at its 3'-end. Intriguingly, expansions that carry these interruption motifs correlate with an epileptic seizure phenotype and are unstable despite the theory that interruptions are expected to stabilize expanded repeats. To examine the apparent contradiction of unstable, interruption-positive SCA10 expansion alleles and to determine whether the instability originates outside of the interrupted region, we sequenced approximately 1 kb of the 5'-end of SCA10 expansions using the ATCCT-PCR product in individuals across multiple generations from four SCA10 families. We found that the greatest instability within this region occurred in paternal transmissions of the allele in stretches of pure ATTCT motifs while the intervening interrupted sequences were stable. Overall, the ATCCT interruption changes by only one to three repeat units and therefore cannot account for the instability across the length of the disease allele. We conclude that the AT-rich interruptions locally stabilize the SCA10 expansion at the 5'-end but do not completely abolish instability across the entire span of the expansion. In addition, analysis of the interruption alleles across these families support a parsimonious single origin of the mutation with a shared distant ancestor.